Introduction to the Mechanics of Space Robots - Genta, Giancarlo; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
Based on lecture notes on a space robotics course, this book offers a pedagogical introduction to the mechanics of space robots. After presenting an overview of the environments and conditions space robots have to work in, the author discusses a variety of manipulatory devices robots may use to perform their tasks. This is followed by a discussion of robot mobility in these environments and the various technical approaches. The last two chapters are dedicated to actuators, sensors and power systems used in space robots. This book fills a gap in the space technology literature and will be useful for students and for those who have an interest in the broad and highly interdisciplinary field of space robotics, and in particular in its mechanical aspects.
Preface -- Contents -- Symbols -- Physical constants -- Acronyms -- 1 Introduction -- 2 Space and planetary environment -- 3 Manipulatory devices -- 4 Mobility on planetary surfaces -- 5 Wheeled vehicles and rovers -- 6 Non-wheeled vehicles and rovers -- 7 Actuators and sensors -- 8 Power systems -- Bibliography -- A Equations of motion in the configuration and state spaces -- B Equations of motion for continuous systems -- Index.
Keywords: Physics; Astronomy; Astronautics; Physics; Astronomy, Astrophysics and Cosmology; Aerospace Technology and Astronautics; Control, Robotics, Mechatronics